A new genus and species of Prosopistomatidae (Insecta: Ephemeroptera) from mid-Cretaceous Myanmar amber. (April 2018) - Lin, Qingqing; Shih, Chungkun; Zhao, Yunyun; Ren, Dong
Abstract: A new genus and species, Proximicorneus rectivenius gen. et sp. nov., in the family Prosopistomatidae of Ephemeroptera, is described from the mid-Cretaceous Myanmar (Burmese) amber. The new taxon is established primarily based on the following characters: Forewing Rs veins branched two times and AA vein situated almost at the tornus, legs well-developed with normal femur, tibia and 3-segmented tarsus, claws with one acute and hooked, the other blunt and straight, paracercus short and cerci multi-segmented. The new amber mayfly is the only and the earliest fossil record of Prosopistomatidae hitherto, dating back to the mid-Cretaceous and indicating the long-term presence of Prosopistomatidae in the Oriental region. This finding not only broadens the diversity of Prosopistomatidae, but also provides important morphological characters to enhance our understanding of the early evolutionary development of the Prosopistomatidae.